Heterodimer magnetic nanoparticles-carbon nanotubes with tunable magnetic properties - Monsalve, Leandro Nicolas (2017)
This work proposes an easy and scalable convergent synthesis method to obtain heterodimers formed by multi-walled carbon nanotubes and magnetic nanoparticles via carbon-nitrogen bonds. Magnetic nanoparticles were synthesized by solvothermal method. Heterodimers were characterized by X-ray diffraction, Fourier Transform Infrared Spectroscopy, Transmission Electronic Microscopy and magnetic properties. The magnetic nanoparticles have a mixed crystal structure, mostly formed by maghemite and a small fraction of hematite. Infrared Spectroscopy and Transmission Electronic Microscopy confirm the formation of heterodimer magnetic nanoparticles—carbon nanotubes via covalent bonds. Magnetic measurement indicates that it is possible to adjust the magnetic response according to the final application.